Work attitude among Malaysian academicians in the public Universities: a social network analysis - Mohd. Asrah, Norhaidah (Canadian Center of Science and Education, 2014)
This study dealt with a social network analysis approach to comprehend the work attitude amongst academicians in the Malaysian public universities. This work attitude presented the psychological attachment between the employee and the organization. The organizational commitment and workplace spirituality amongst the academicians were highlighted here. A total of 40 factors were found to represent four groups of workplace spirituality and organizational commitment. The similarity amongst the factors was measured with two different kinds of associations. The best measure of association, which was the Tschuprow's measure of association, showed better results than the other measure in measuring the correlation amongst the factors. The connections and relationships amongst the factors were studied by using minimum spanning trees (MST). The interpretation of the MST was conducted by using the overall centrality measure.